Rethinking recovery and desistance processes: developing a social identity model of transition. (2nd January 2019) - Kay, Christopher; Monaghan, Mark
Abstract: Background: In recent years, the role of social identity (or identities which are developed through involvement in social groups with others), has received increasing attention in relation to recovery from substance abuse disorders. However, it is also widely noted that the transformation of one's social identitie(s) is vital for the cessation of other, non-addictive behaviours, such as offending. Interestingly, the discussion of the role of social identity tansformation in relation to both desistance and recovery simultaneously has seldom been undertaken.Methods: Drawing on primary research consisting of 20 double narrative interviews with young adult offenders on an Intensive Community Order, the paper builds upon the two most prominent social identity models surrounding addictive behaviour, the Social Identity Model of Recovery and the Social Identity Model of Cessation Maintenance in order to develop a social identity model which aids our understanding of desistance and recovery processes.Results: The paper presents a Social Identity Model of Transition (SIMOT), allowing for the synergies between desistance and recovery as processes of transition to come to light.Conclusion: SIMOT allows for an understanding of the role of social identity transformation in the transient nature of desistance and recovery processes. The model allows for an examination of the impact of macro and micro contextual factors on desistance and recovery processes in a way which has seldom been possible with the currently available models.